Homicide and criminal careers: an empirical study on serial murderers - Campedelli, Gian Maria (Routledge handbook of homicide studies, 2024)
The criminal careers framework has revolutionized the way in which criminologists conceptualize and study offending behaviors and the temporal trajectories of crime. In this chapter, we adopt the criminal career perspective to study a specific offender type that continues to attract great interest from the public and academia: the serial murderer. Relying on a sample of 2,888 serial killers active in the United States from 1940 to 2022, we propose an analytical framework to examine trends in career duration and homicide frequency. We first focus on the entire sample and then on three comparative accounts: (1) male and female serial killers, (2) serial killers across decades of activity and (3) serial killers across different onset ages. We offer numerous findings. Male murderers are shown, on average, to have slightly longer careers than female murderers. We also show that those who begin to kill in their teens tend to kill for longer, although their homicide frequency is lower compared to those who begin at a later age. Additionally, we find that the later in life an offender starts their sequence of murders, the shorter their career typically is. Our results highlight the importance of considering individual as well as macro-level factors in dissecting serial murder and testify to the relevance of the criminal career paradigm as a valuable tool to gather knowledge on this complex phenomenon.